1992
DOI: 10.1128/jvi.66.12.7538-7542.1992
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization of diverse human immunodeficiency virus type 1 variants by an anti-V3 human monoclonal antibody

Abstract: The third variable region (V3) of the HIV-1 gpl20 envelope glycoprotein is thought to induce potent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
158
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(167 citation statements)
references
References 41 publications
9
158
0
Order By: Relevance
“…MAbs used. MAb b12 was isolated by phage display (42), MAb 447-52D was isolated through hybridoma formation (41), and the remaining MAbs used here were isolated by VH and VL gene amplification from single B cells (11,43,44). The VH and VL gene usages of b12, PG9, 447-52D, and FI6 are provided in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…MAbs used. MAb b12 was isolated by phage display (42), MAb 447-52D was isolated through hybridoma formation (41), and the remaining MAbs used here were isolated by VH and VL gene amplification from single B cells (11,43,44). The VH and VL gene usages of b12, PG9, 447-52D, and FI6 are provided in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Interactions of 447-52D BCRs with recombinant Env. The V3 loop is a target of neutralizing antibodies against HIV-1, and MAb 447-52D is one of the most extensively characterized anti-V3 NAbs (41,(63)(64)(65)(66)(67). Although 447-52D is less potent and broad in its neutralizing activity than b12 or PG9 (25,68), it does neutralize diverse HIV-1 isolates.…”
Section: Expression and Functionality Of Exogenous Bcrs On The Surfacmentioning
confidence: 99%
See 1 more Smart Citation
“…The mAbs used here were originally isolated in our lab from peripheral blood mononuclear cells (PBMCs) of HIV-1-infected individuals, using cellular (hybridoma) techniques described previously. The mAbs used in this study were re-expressed using recombinant technology as IgG 1 [21][22][23][24][25][26][27]. Monoclonal Abs 1357 [28], 1361 [28], 2158 [29], and 830A [26] are specific for the V2i epitope of gp120 as defined in Spurrier et al [30].…”
Section: Antibodiesmentioning
confidence: 99%
“…Antisera that exhibit broadly neutralizing activity against diverse HIV-1 isolates have been observed in some long-term non-progressors (LTNP) (Braibant et al, 2006;Cecilia et al, 1999;Pilgrim et al, 1997). However, they are rare; despite over two decades of AIDS research, only a handful of broadly reactive Nabs (BR-Nabs) have been identified, including monoclonal antibodies (mAbs) b12, 2G12, 447-52D, 2F5, 4E10 and m48 (Gorny et al, 1992;Muster et al, 1993;Roben et al, 1994;Stiegler et al, 2001;Trkola et al, 1996;Zhang et al, 2006;Zwick et al, 2001). While the first three antibodies are gp120-specific, the latter three target gp41.…”
Section: Introductionmentioning
confidence: 99%